Trade‐offs between seed output and life span – a quantitative comparison of traits between annual and perennial congeneric species. Issue 1 (27th July 2015) - Vico, Giulia; Manzoni, Stefano; Nkurunziza, Libère; Murphy, Kevin; Weih, Martin
Summary: Perennial plants allocate more resources belowground, thus sustaining important ecosystem services. Hence, shifting from annual to perennial crops has been advocated towards a more sustainable agriculture. Nevertheless, wild perennial species have lower seed production than selected annuals, raising the questions of whether there is a fundamental trade‐off between reproductive effort and life span, and whether such trade‐off can be overcome through selection. In order to address these questions and to isolate life span from phylogenetic and environmental factors, we conducted a meta‐analysis encompassing c . 3000 congeneric annual/perennial pairs from 28 genera. This meta‐analysis is complemented with a minimalist model of long‐term productivity in perennial species. Perennials allocate more resources belowground and less to seeds than congeneric annuals, independently of selection history. However, existing perennial wheat and rice could achieve yields similar to annuals if they survived three years and each year doubled their biomass, as other perennial grasses do. Selected perennial crops maintain the large belowground allocation of wild perennials, and thus can provide desired regulatory ecosystem services. To match the seed yield of annuals, biomass production of perennial grains must be increased to amounts attained by some perennial grasses – if this goal can be met, perennial crops can provide a more sustainable alternative to annuals.